Higher education in Malaysia and Australia 2005: A regional research forum on higher education. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2005)

(untitled)
Professor Morshidi Sirat, Director, IPPTN and Professor Ambigapathy Pandian, Associate Research Fellow, IPPTN were invited to present their working papers at the inaugural Malaysia-Australia Higher Education Forum held at the University of Wollongong, Australia, 2-4th November 2005.